(untitled) (Oil and Gas Engineering, 2017)
In this study, we carried out theoretical studies to identify and determine the influence of the most important factors and choose the best geometrical parameters of the drilling apparatus under reduced hydrostatic pressure in the wellbore, which provided high efficiency of drilling. Theoretical studies of the flow of active and passive streams and washing liquid reservoir, and mixtures thereof through constructive elements allow setting equipment interconnection patterns oil drilling efficiency of the device parameters and operating conditions for drilling with reduced hydrostatic pressure in the wellbore. On the basis of theoretical studies of the optimal design features of downhole drilling equipment, which is part of the drilling apparatus underreduced hydrostatic pressure in the wellbore. A scheme of ground placement of the equipment used to actu-ate downhole drilling equipment. Keywords: drilling under reduced hydrostatic pressure jet pump, downhole drilling equipment, ground equipment to actuate downhole drilling equipment.